Adult T-Cell Leukemia/Lymphoma-Related Ocular Manifestations: Analysis of the First Large-Scale Nationwide Survey - Kamoi, Koju; Okayama, Akihiko; Izumo, Shuji; Hamaguchi, Isao; Uchimaru, Kaoru; Tojo, Arinobu; Ohno-Matsui, Kyoko (Frontiers in Microbiology, 2019)
Adult T-cell leukemia/leukemia (ATL) is a rare and aggressive T-cell malignancy with a high mortality rate, resulting in a lack of information among ophthalmologists. Here, we investigated the state of ophthalmic medical care for ATL and ATL-related ocular manifestations by conducting the first large-scale nationwide survey in Japan. A total of 115 facilities were surveyed, including all university hospitals in Japan that were members of the Japanese Ophthalmological Society and regional core facilities that were members of the Japanese Ocular Inflammation Society. The collected nationwide data on the state of medical care for ATL-related ocular manifestations and ATL-associated ocular findings were categorized, tallied, and analyzed. Of the 115 facilities, 69 (60%) responded. Overall, 28 facilities (43.0%) had experience in providing ophthalmic care to ATL patients. ATL-related ocular manifestations were most commonly diagnosed “based on blood tests and characteristic ophthalmic findings”. By analyzing the 48 reported cases of ATL-related ocular manifestations, common ATL-related ocular lesions were intraocular infiltration (22 cases, 45.8%) and opportunistic infections (19 cases, 39.6%). All cases of opportunistic infection were cytomegalovirus retinitis. Dry eye (3 cases, 6.3%), scleritis (2 cases, 4.2%), uveitis (1 case, 2.1%), and anemic retinopathy (1 case, 2.1%) were also seen. With regard to distribution, a large number of ATL cases (31 cases, 64.6%) were seen in central and metropolitan areas. In conclusion, intraocular infiltration and cytomegalovirus retinitis are common among ATL patients, and ophthalmologists should keep these findings in mind in their practice.